2008
DOI: 10.1186/1479-5876-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Transient T cell depletion causes regression of melanoma metastases

Abstract: Background: Cognate immunity against neoplastic cells depends on a balance between effector T cells and regulatory T (Treg) cells. Treg cells prevent immune attack against normal and neoplastic cells by directly suppressing the activation of effector CD4 + and CD8 + T cells. We postulated that a recombinant interleukin 2/diphtheria toxin conjugate (DAB/IL2; Denileukin Diftitox; Ontak) may serve as a useful strategy to deplete Treg cells and break tolerance against neoplastic tumors in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 22 publications
2
92
0
Order By: Relevance
“…We and others saw impressive augmentation of T-cell-based immunotherapies despite incomplete Treg depletion, 46 and recent clinical trials have documented similar changes in Treg populations after CD25-based targeting using CD25-directed immunotoxins LMB-2 47 or RFT5-SMPT-dgA. 48,49 We posit that neither complete nor prolonged Treg depletion is necessary to improve the efficacy of adoptive immunotherapy and that Treg depletion mirroring the degree we show here to improve outcomes in the context of adoptive immunotherapy is readily translatable to the clinic. RhIL-7 therapy, administered without Treg depletion, enhanced both the number and function of adoptively transferred T cells and significantly enhanced outcomes in both Rag1 Ϫ/Ϫ and Thy-B recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We and others saw impressive augmentation of T-cell-based immunotherapies despite incomplete Treg depletion, 46 and recent clinical trials have documented similar changes in Treg populations after CD25-based targeting using CD25-directed immunotoxins LMB-2 47 or RFT5-SMPT-dgA. 48,49 We posit that neither complete nor prolonged Treg depletion is necessary to improve the efficacy of adoptive immunotherapy and that Treg depletion mirroring the degree we show here to improve outcomes in the context of adoptive immunotherapy is readily translatable to the clinic. RhIL-7 therapy, administered without Treg depletion, enhanced both the number and function of adoptively transferred T cells and significantly enhanced outcomes in both Rag1 Ϫ/Ϫ and Thy-B recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical trials, denileukin diftitox was administered in patients with metastatic carcinoma or melanoma (Dannull et al, 2005;Zou, 2006;Mahnke et al, 2007;Morse et al, 2008;Rasku et al, 2008). A reduction of circulating FOXP3 þ Treg was generally obtained, but very few clinical responses were observed.…”
Section: Foxp3 þ Treg and Cancer Treatmentmentioning
confidence: 99%
“…Thus far, clinical studies in which Ontak was administered to melanoma patients showed that it may reduce the number of circulating Tregs and cause regression of melanoma metastases (27)(28)(29).…”
mentioning
confidence: 99%